One dummy won't get it: The impact of training programme type and duration on the employment chances of the unemployed in Ireland - Seamus McGuinness; Philip J. O'Connell; Elish Kelly (The Economic and Social Research Institute (ESRI), 2011)
In the extensive literature on the employment impact of public-sponsored training programmes for the unemployed, insufficient attention has been paid to the differential impact of different types of programmes and training duration. This paper uses a unique dataset, which tracks the labour market position of a cohort of unemployment benefit claimants for almost two years, to evaluate the impact of a range of government-sponsored training courses in Ireland. Overall, we found that those who participated in training were less likely to be unemployed at the end of the two-year study period. However, the average effect of training varied by the type and duration of training received. In general, we found strong positive effects for job-search skills training and medium-to high-level skills courses, a more modest positive effect for general vocational skills programmes (which are not strongly linked to demand in the labour market) and less consistent effects with respect to low-level skills training. We also found that training episodes with lower duration had a more positive impact, with the exception of high-level skills training programmes where longer training durations appear more effective. The results suggest that, in the Irish context, there are potentially substantial benefits to re-orientating unemployment training provision away from standard classroom vocational training towards the medium to highlevel skill end of the market and demonstrate that, in most cases, training durations can be reduced without lowering the effectiveness of the interventions.
Keywords: 330; unemployment; activation; training; Arbeitslosigkeit; Arbeitsmarktpolitik; Qualifikation; Weiterbildung; Wirkungsanalyse; Irland